Implikasi Putusan Praperadilan Terhadap Perintah Penetapan Tersangka - Surya Pandu Baskara; Alfitra Alfitra (JOURNAL of LEGAL RESEARCH, 2019)
AbstractCriminal Procedure Law is a collection of provisions on how to investigate, investigate, prosecute, and prosecute someone who is considered guilty and commits a criminal law violation. Pretrial in this case is a mechanism in protecting the rights of the accused in a criminal case. The pretrial object that has been regulated in Law No. 8 of 1981 concerning the Criminal Procedure Code. This research uses descriptive research and uses a juridical-normative research approach. The results showed that the judge ordered the Corruption Eradication Commission as a pretrial respondent to designate several suspects as suspects in a Century Bank corruption crime. Judges interpret pre-judicial authority broadly, not limited to the provisions of the Criminal Procedure Code, Constitutional Court Decision Number 21 / PUU-XII / 2014, and Supreme Court Regulation (PERMA) Number 4 of 2016 concerning the Prohibition of Judicial Review Judgment. However, the presence of PERMA No. 4 of 2016 has eliminated ordinary legal or extraordinary remedies against pretrial decisions that have implications that these decisions must be carried out based on the governing provisions.Keywords: Pretrial, Suspect Determination Order, Legal Discovery